2014
DOI: 10.17221/916/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen efficiency of spring barley in long-term experiment

Abstract: The aim of this study was to evaluate nitrogen (N) efficiency from different organic and mineral fertilizers applied to the spring barley. Dry matter yield, N content and N uptake of spring barley from 16 years of experiments at two sites in the Czech Republic with different soil and climatic conditions were analyzed. For assessing of nitrogen efficiency nitrogen utilization efficiency (NUtE, kg/kg), recovery efficiency of applied N (%), agronomic efficiency of applied N (kg/kg) and summary N balances (ΣΔN, kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
3
10
0
Order By: Relevance
“…Similarly, as in the study with barley of S h e j b a l o v á et al (2014), the present experiment confirmed a tendency of yield increases at the low fertile location after mineral nitrogen application. Similar tendency of yield increases after mineral nitrogen application on the low fertile location in this experiment with barley were obtained (Shejbalová et al, 2014). Thousand kernel weight is greatly determined by climatic conditions, particularly high temperature during the final phase of grain filling can negatively affect this yield parameter (L ó p e z -B e l l i d o et al, 1998; R h a r r a b t i et al., 2003), which may explain why there were high differences between years at S1.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, as in the study with barley of S h e j b a l o v á et al (2014), the present experiment confirmed a tendency of yield increases at the low fertile location after mineral nitrogen application. Similar tendency of yield increases after mineral nitrogen application on the low fertile location in this experiment with barley were obtained (Shejbalová et al, 2014). Thousand kernel weight is greatly determined by climatic conditions, particularly high temperature during the final phase of grain filling can negatively affect this yield parameter (L ó p e z -B e l l i d o et al, 1998; R h a r r a b t i et al., 2003), which may explain why there were high differences between years at S1.…”
Section: Discussionsupporting
confidence: 85%
“…From an exclusively economic point of view, it is estimated that a 1% improvement of N efficiency in cereals could save over US$200 million in N fertilizer costs, worldwide [71]. Therefore, fertilizing crops with excessive N rates not only poses environmental hazards, which is gradually becoming a serious cause for concern, but also leads to economic losses [44,54,[71][72][73][74].…”
Section: Resultsmentioning
confidence: 99%
“…Nogalska et al (2014) reported that an increase in MBM dose from 1.5 t/ha to 2.5 t/ha had no significant effect on the yields of the four analysed crops, and concluded that in soils with satisfactory nutrient content, MBM dose of 1.0 t/ha or 1.5 t/ha is sufficient, and a further increase in MBM fertilization could increase economic burden for farmers and environmental risks. Spring barley is a crop species with a short growing season and a weak root system, which increases the risk of nitrogen losses to the environment (Shejbalová et al 2014). Mineral nitrogen, in particular nitrates, pose the greatest risk to the environment.…”
Section: Resultsmentioning
confidence: 99%